Desain Pembelajaran Inovatif Berbasis Masalah untuk Meningkatkan Kemampuan Berpikir Kritis peserta didik - Luqyanah Khansa; Kayla Arifa; Gusmaneli Gusmaneli (CV.ITTC INDONESIA, 2025)
This study aims to design an innovative problem-based learning (PBL) model to enhance students' critical thinking skills. The design process involves several stages, including needs analysis, design, development, implementation, and evaluation. The PBL model is designed to encourage students to actively engage in solving real-world problems, thereby stimulating their critical thinking abilities. Data were collected through observation, interviews, and tests to assess the effectiveness of the PBL model. The results showed that the innovative PBL design significantly improved students' critical thinking skills. This research implies that PBL can be an effective approach in fostering critical thinking skills, which are essential for students' academic and professional success.